MY SAY: Working towards 2020 and beyond - Abd Razak, Dzulkifli (2010)
In any endeavour, vision is vital to navigate the estuaries of peril and opportunity. Foresight is a tool when the realities of tomorrow are conceptualised today, thus reducing the level of uncertainty. This becomes even more important as our horizons keep changing and Moore's Law epitomises the speed of our technical progress. For example, in less than two decades, cellphones, laptops and the Internet have become a way of life that was inconceivable in the past.